IMMU-51. THE COMBINATION OF CCR2 ANTAGONIST AND PD-1 BLOCKADE PROLONGS SURVIVAL IN IMMUNE CHECKPOINT INHIBITOR RESISTANT GLIOMAS. (5th November 2018) - Flores-Toro, Joseph; Luo, Defang; Gopinath, Adithya; Campbell, James; Charo, Israel; Singh, Rajinder; Schall, Thomas; Harrison, Jeffrey
Abstract: INTRODUCTION: Immuno-therapy directed at the PD-1/PD-L1 axis has produced significant treatment advances in various human cancers. Unfortunately, this progress has not extended to glioblastoma, with recent clinical trials failing to show efficacy of anti-PD-1 monotherapy in recurrent tumors. Commonly employed murine glioma models exhibit varied responsiveness to anti-PD-1 monotherapy, e.g. GL261 gliomas are sensitive while KR158 tumors are resistant. Previously, we reported that combining PD-1 blockade with either chemokine receptor CCR2 deficiency or a CCR2 antagonist improved survival over anti-PD-1 monotherapy in GL261 gliomas. This was associated with reduced numbers of MDSCs within tumors. The current study evaluated the combination of PD-1 blockade and a novel CCR2 antagonist in anti-PD-1 resistant gliomas. OBJECTIVE: Determine if combination anti-PD-1/CCR2 antagonist therapy is an effective treatment in anti-PD-1 insensitive gliomas. METHODS: Overall survival and immune cell characteristics were determined in KR158 and 005GSC gliomas established in either CCR2 deficient or wild type mice treated with CCR2 antagonist (CCX872) and/or PD-1 blockade. RESULTS: CCR2 deficiency unmasked an anti-PD-1 survival benefit in KR158 glioma-bearing mice. CCX872 increased median survival as a monotherapy in KR158 tumor-bearing animals, and significantly increased median and durable overall survival when combined with anti-PD-1. In 005GSC tumors, the combination of CCX872 and anti-PD-1 prolonged median survival time. Increases in overall CCR2 + cells and CD11b + /Ly6C hi myeloid derived suppressor cells (MDSC, known to be CCR2 + ) were evident in the bone marrow of CCR2-deficient mice. Additionally, these mice exhibited decreased MDSCs within established gliomas. The data demonstrate CCX872/anti-PD-1 synergize to increase survival in clinically relevant glioma models via reduced MDSC infiltration, resulting in a tumor microenvironment favorable for anti-PD-1 efficacy. CONCLUSION: The combination of CCX872 and anti-PD-1 is effective in clinically relevant murine glioma models, providing a basis on which to progress this novel combinatorial treatment toward early phase human trials.